Penyelesaian Tindak Pidana Korupsi Oleh Subjek Militer Saat Sedang Menduduki Jabatan Sipil - Vania Oktaviani Dewi; Irwan Triadi (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This research was motivated by the emergence of the case of the KPK naming a suspect as the head of Basarnas who was a member of the military but currently holding a civilian position. The aim of this research is to answer the Corruption Eradication Committee's authority to participate in dealing with criminal acts of corruption in the military environment and also aims to find ideal law enforcement for military members who commit criminal acts of corruption. In this research, it was found that there were conflicting regulations regarding law enforcement against military members who committed criminal acts of corruption. However, the Corruption Eradication Commission (KPK) still has the authority to handle legal matters relating to criminal acts of corruption within the military in accordance with statutory provisions. Apart from that, it is best to resolve criminal acts of corruption in the military environment through corruption courts in accordance with statutory provisions.